Tourism, technology and competitive strategies - Poon, Auliana (CAB International WallingfordGB, 1993)
Looks at the evolution of mass tourism and the transformation toward a new tourism. Analyses the key imperatives for change viz. limits to growth and the emergence of a new global 'best practice'; new consumers; and, new technologies. Identifies the important trend towards 'diagonalization' in the tourism industry and explores the implications of new tourism for tour operators, travel agents and hotels. Explores competitive strategies for industry players and tourism destinations.